Berlin Psychoanalytic : psychoanalysis and culture in Weimar Republic Germany and beyond - Fuechtner, Veronika, 1969- (Weimar and now ;, 2011)
100 years after the Berlin Psychoanalytic Institute was established, this book recovers the cultural and intellectual history connected to this vibrant organization and places it alongside the London Bloomsbury group and the Paris surrealist circle as a crucial chapter in the history of modernism.